ANTI-FUNGAL ACTIVITY TEST OF PLETEKAN LEAVES LIQUID SOAP (Ruellia tuberosa L.) ON CANDIDA ALBICANS - Ahmad Fuad Masduqi; Mighfar Syukur (Universitas Muhammadiyah Magelang, 2021)
The fungus Candida albicans is a pathogenic species that causes candidiasis. Pletekan plant has potential as a medicinal plant. This plant is proven to have one of the effects as an antimicrobial. The purpose of this study was to determine whether the pletekan leaf extract liquid soap could inhibit the growth of Candida albicans and whether there were differences in the antifungal activity of the liquid soap pletekan leaf extract at a concentration of 20%, 40%, and 60%. This study used maceration extraction methods, screening for secondary metabolites and continued with TLC tests. Liquid soap formulations from extracts with different concentrations. Furthermore, the research was carried out to test the antifungal activity by using the good method on liquid soap for the pletekan leaf extract against the growth of Candida albicans. Screening and TLC results showed that the pletekan leaf extract contained flavonoids, steroids, triterpenoids, and alkaloids. Liquid soap preparations including organoleptic, pH, homogeneity, and viscosity are included in the criteria for the Indonesian National Standard. The results showed that pletekan leaf extract in a liquid soap preparation could inhibit the growth of Candida albicans. The results of statistical tests show that the data are normally distributed and homogeneous. There were differences in the antifungal activity of the liquid soap for pletekan leaf extract with a concentration of 20%, 40%, and 60% which resulted in a succession of 8,456mm; 12,186mm; and 14,293mm. The antifungal activity showed that the extract concentration was directly proportional to the resulting inhibition zone